Django datatable builder: an improved approach for implementing dynamic tables in Django - BIZARRIA, Romero Ramsés Cartaxo (2025)
Dynamic tables serve as essential components in modern web applications, but integrating rich client-side JavaScript libraries with server-side frameworks like Django presents significant challenges. Existing integration libraries often suffer from being unmaintained, incomplete, or architecturally restrictive. This paper presents Django Datatable Builder, a Python library designed to solve this problem by encapsulating the complexity of DataTables.js integration using the Builder design pattern. The library provides a unified, Pythonic API that handles both client and server-side logic, abstracting away repetitive tasks like request parsing, queryset filtering, and response formatting, while adding high-level features such as custom actions and extensible filters. Its effectiveness is demonstrated through the implementation of a sample college management system, which showcases the library’s ability to reduce development time, improve code maintainability, and enforce security best practices across various real-world scenarios. The result is a powerful tool that enables developers to build secure, consistent, and feature-rich dynamic tables with minimal code.